The role of docetaxel in the treatment of non-small cell lung cancer lung cancer: an update. (1st November 2016) - Matikas, A.; Georgoulias, V.; Kotsakis, A.
ABSTRACT: Introduction : Non-small cell lung cancer lung cancer (NSCLC) is a devastating disease, with poor prognosis for patients with metastatic disease. The management of these patients has evolved during the past decade, challenging the role of cytotoxic chemotherapy as the only available treatment option. Nevertheless, chemotherapy still retains a dominant position for the majority of both treatment naïve and pretreated patients. Among the chemotherapeutic agents, docetaxel is one of the most commonly used in 1st and subsequent treatment lines, even in the current era of precision medicine. Areas covered : We searched Medline, Embase, Scopus and Cochrane Library for randomized phase III trials that evaluated docetaxel in various clinical settings of NSCLC and for meta-analyses of such trials and we present all relevant data regarding the pharmacology and clinical use of docetaxel in NSCLC. Expert commentary : Despite its diminishing role, docetaxel in combination with novel targeted agents remains an important option of the therapeutic armamentarium in advanced NSCLC.